2005
DOI: 10.1348/000709905x37181
|View full text |Cite
|
Sign up to set email alerts
|

Coursework selection: A frame of reference approach using structural equation modelling

Abstract: Background. Choice behaviour has far‐reaching consequences on students' educational careers. Previous models on course selection for example, the model of achievement‐related choices (Wigfield & Eccles, 2000) and of self‐efficacy theory (Bandura, 1997), stress the importance of ability perceptions (self‐concept of ability) as major determinants of choice. Aim. This article suggests a model of course selection, which assumes that comparisons within an internal frame of reference (as proposed by Marsh, 1986, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 41 publications
(89 reference statements)
2
26
0
Order By: Relevance
“…However, other types of behavior (for example, achievement-related choices) are also assumed -and have been demonstrated -to be influenced by expectancies (see Dickhäuser, Reuter and Hilling 2005). Future research investigating how individuals rely on their performance expectation when making achievement-related choices should also take the importance of certainty into account.…”
Section: Discussionmentioning
confidence: 99%
“…However, other types of behavior (for example, achievement-related choices) are also assumed -and have been demonstrated -to be influenced by expectancies (see Dickhäuser, Reuter and Hilling 2005). Future research investigating how individuals rely on their performance expectation when making achievement-related choices should also take the importance of certainty into account.…”
Section: Discussionmentioning
confidence: 99%
“…For example, someone trying to self-evaluate how verbally talented he or she is may choose his/her math ability as a comparison standard even if choosing math as a (worse-off) standard may not be beneficial to the actual self. Dickhäuser, Reuter, and Hilling (2005) and Nagy et al (2006) showed that the probability of choosing a particular course in school is positively affected by high achievement in corresponding subjects and negatively affected by high achievement in non-corresponding subjects (i.e., influenced by dimensional comparisons). Imagine a student who has to decide whether he/she wants to concentrate on language or on science courses.…”
Section: The Dimensional Comparison Theorymentioning
confidence: 99%
“…They rather pointed out that the achievement and self-concept variables between similar subjects within a certain domain were likely to correlate in a significantly positive manner, thus indicating small assimilative comparison effects (Dickhäuser, 2003;Dickhäuser, Reuter & Hilling, 2005;Möller, Streblow, Pohlmann & Köller, 2006;Schilling, Sparfeldt & Rost, 2004). However, a cross-cultural analysis of the relations between self-concept and achievement in science and mathematics helps to draw a more differentiated picture.…”
Section: Introductionmentioning
confidence: 99%